Evaluating the Impact of Wildlife Shelter Management on the Genetic Diversity of Erinaceus europaeus and E. roumanicus in Their Contact Zone - Ploi, Kerstin; Curto, Manuel; Bolfíková, Barbora Černá; Loudová, Miroslava; Hulva, Pavel; Seiter, Anna; Fuhrmann, Marilene; Winter, Silvia; Meimberg, Harald (Animals, 2020)
Hedgehogs are among the most abundant species to be found within wildlife shelters and after successful rehabilitation they are frequently translocated. The effects and potential impact of these translocations on gene flow within wild populations are largely unknown. In this study, different wild hedgehog populations were compared with artificially created "shelter populations", with regard to their genetic diversity, in order to establish basic data for future inferences on the genetic impact of hedgehog translocations. Observed populations are located within central Europe, including the species Erinaceus europaeus and E. roumanicus. Shelters were mainly hosting one species; in one case, both species were present syntopically. Apart from one exception, the results did not show a higher genetic diversity within shelter populations, indicating that individuals did not originate from a wider geographical area than individuals grouped into one of the wild populations. Two shelters from Innsbruck hosted individuals that belonged to two potential clusters, as indicated in a distance analysis. When such a structure stems from the effects of landscape elements like large rivers, the shelter management-related translocations might lead to homogenization across the dispersal barrier.
Keywords: hedgehog; animal shelter; genotyping by amplicon sequencing; translocation